Diagnóstico sectorial de la sección de actividades de descafeinado, tostado y elaboración de productos de café (C1079.11), distrito 11D06, provincia de Loja - Ojeda Calva, Leila Kathiuska (2024)
The sectoral diagnosis is an instrument that allows a sector to be characterized in an organized and concise manner through the use of tools such as management indicators and key factors, which generate pertinent information to evaluate and analyze the business performance of a company within an economic sector. Given the degree of relevance, the main objective of this study was to carry out a sectoral diagnosis of the decaffeination, roasting, and production of coffee products in district 11D06, province of Loja. To achieve this, a non-exploratory and cross-sectional methodology was applied, with a mixed approach. The research instrument used was a survey, which was administered to 27 microenterprises dedicated to the coffee industry with the ISIC code C1079.11. To normalize atypical data, the winsorizing technique was applied. The main results showed that the coffee industry does not have optimal solvency, as it registers a liquidity index of $0.93, indicating a limited capacity to cover short-term commitments. Additionally, it has a high level of debt (86%) that may imply financial risk. Despite this, the sector has a surplus of resources to meet payments to employees, suppliers, etc., and a return on equity of 21.12%, which suggests a positive profit in relation to share capital. In conclusion, the analyzed coffee industry faces several financial challenges, such as low liquidity and high debt. However, it has positive working capital and an acceptable return on equity. This suggests that, while there are areas for improvement, the industry has some financial stability and potential to improve its profitability through more efficient management of its assets and liabilities.